Climate change impacts of power generation from residual biomass. (June 2016) - Giuntoli, J.; Agostini, A.; Caserini, S.; Lugato, E.; Baxter, D.; Marelli, L.
Abstract: The European Union relies largely on bioenergy to achieve its climate and energy targets for 2020 and beyond. We assess, using Attributional Life Cycle Assessment (A-LCA), the climate change mitigation potential of three bioenergy power plants fuelled by residual biomass compared to a fossil system based on the European power generation mix. We study forest residues, cereal straws and cattle slurry. Our A-LCA methodology includes: i) supply chains and biogenic-CO2 flows; ii) explicit treatment of time of emissions; iii) instantaneous and time-integrated climate metrics. Power generation from cereal straws and cattle slurry can provide significant global warming mitigation by 2100 compared to current European electricity mix in all of the conditions considered. The mitigation potential of forest residues depends on the decay rate considered. Power generation from forest logging residues is an effective mitigation solution compared to the current EU mix only in conditions of decay rates above 5.2% a −1 . Even with faster-decomposing feedstocks, bioenergy temporarily causes a STR(i) and STR(c) higher than the fossil system. The mitigation potential of bioenergy technologies is overestimated when biogenic-CO2 flows are excluded. Results based solely on supply-chain emissions can only be interpreted as an estimation of the long-term (>100 years) mitigation potential of bioenergy systems interrupted at the end of the lifetime of the plant and whose carbon stock is allowed to accumulate back. Strategies for bioenergy deployment should take into account possible increases in global warming rate and possible temporary increases in temperature anomaly as well as of cumulative radiative forcing. Highlights: Bioenergy LCAs should be dynamic, include all climate forcers and multiple metrics. Excluding biogenic-CO2 overestimates bioenergy climate change mitigation potential. Power from straw and slurry mitigates climate change compared to fossil alternative in 2100. Decay rates of forest residues influence magnitude of climate change mitigation. Power from slow-decaying forest residues increases global warming rate and magnitude in 2100.